Biomaterials for Clinical Applications - Bhatia, Sujata K. (Springer New York : Imprint: Springer, 2010)
This book is organized according to the World Health Organization's report of the top 10 causes of death worldwide, and lays out opportunities for both biomaterials scientists and physicians to confront each of these leading contributors to mortality. The introductory chapter discusses the global burden of disease. Each of the subsequent ten chapters focuses on a specific disease process, beginning with the leading cause of death worldwide, cardiovascular disease. Each chapter begins by describing diseases in which clinical needs are most pressing, and then envisions how biomaterials can be designed to address these needs. The approach is clinically centered, in contrast to the more technologically centered approached favored by most books in the field. This book bridges the gap between the laboratory and the clinic by identifying needs for biomedical materials in the context of the most prevalent diseases worldwide. Sujata K. Bhatia is a physician-scientist at DuPont Applied BioSciences, and an affiliated faculty member in the Department of Chemical Engineering at the University of Delaware.